Regulation of cold stress and biochemical responses in marigold var. Pusa Narangi Gainda during the winter season - Tejaswi, Rayavarapu; Kumar, Prabhat; Singh, K.P.; Singh, M.C.; Panwar, Sapna; Jain, Ritu; B.K., Tejukumar; Kumar L.N., Vinay (Indian Journal of Horticulture, 2024)
This study aimed to compare various methods to alleviate cold stress and investigate biochemical responses in marigold var. Pusa Narangi Gainda. This study was conducted over two years (2021-2022 and 2022-2023) at the Centre for Protected Cultivation Technology (CPCT), ICAR-Indian Agricultural Research Institute, New Delhi involving the sowing of marigold variety Pusa Narangi Gainda on three different dates. The seedlings were then cultivated under two different growing conditions, using various treatments and their respective combinations. The biochemical responses were assessed and analysed. Results revealed that plants cultivated inside a low plastic tunnel showed the lowest activity of anti-oxidant enzymes, proline content, malondialdehyde content, total phenol content, total soluble sugars and soluble protein content significantly compared to those grown in open field conditions. Additionally, the plants from the sowing date of October 15th recorded the lowest values compared to the other two sowing dates (November 1st and November 15th). Through the examination of different treatments, it was observed that the combination of Chito Oligosaccharide at a concentration of 200 ppm with Arbuscular mycorrhiza recorded the increased anti-oxidant enzyme activity, proline content, total phenol content, total soluble sugars, soluble protein content and reduced malondialdehyde content comparing to the control and other treatments. This study showcases the beneficial effects of using low plastic tunnels in different sowing dates and treatments to increase plant resilience to cold stress.